Managemen Promosi Dalam Meningkatkan Jumlah Siswa di MIS Baja Kuning - Sartika Hutasuhut; Neliwati Neliwati; Muhammad Isa; Hasanuddin Hasanuddin (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
This study aims to determine the management of promotions in increasing the number of students at MIS Baja Kuning. From this objective, it can be seen that promotion strategies and actions taken by madrasah principals, teachers and madrasah staff to promote madrasah so that it becomes an attraction that will increase the number of students. This research was conducted using.a.qualitative.approach. .Data.collection techniques.in.this.study.using interviews, . observation and.documentation. .Data.analysis.was carried out using the stages of the Miles and Huberman model such as: (1) collecting data, (2) reducing data, (3) presenting data, (4) drawing conclusions. The main problem in this study is that madrasah ibtidaiyah still has a small number of students. The analysis of the findings of this study will be carried out according to the type of data collected. After the data was analyzed, there were findings in the study, namely: first, madrasas have education and jupdik committees so that the implementation runs systematically, second, madrasas prepare agendas that must be carried out during the education and jupdik period so that people understand the importance of education, third, madrasas prepare facilities and infrastructure needed so that education and education and education can be carried out properly such as jupdik vehicles and other supporting facilities, fourth, madrasas compile reports on the results of education and education activities